2022
DOI: 10.1002/adom.202200049
|View full text |Cite|
|
Sign up to set email alerts
|

Photo‐Responsive Molecular Junctions Activated by Perovskite/Graphene Heterostructure Electrode

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This phenomenon can induce a range of interesting physical phenomena, such as an optically induced Stark effect, [20] large hysteresis on the gate voltage dependence of the graphene resistance, [19] and enhancement of the photoresponsivity. [21,22] However, to fully exploit the potential of perovskite/graphene structures, a comprehensive understanding of their properties is still needed. High magnetic fields are invaluable for interrogating fundamental physical processes Stable all-inorganic CsPbX 3 perovskite nanocrystals (PNCs) with high optical yield can be used in combination with graphene as photon sensors with high responsivity (up to 10 6 A W −1 ) in the VIS-UV range.…”
mentioning
confidence: 99%
“…This phenomenon can induce a range of interesting physical phenomena, such as an optically induced Stark effect, [20] large hysteresis on the gate voltage dependence of the graphene resistance, [19] and enhancement of the photoresponsivity. [21,22] However, to fully exploit the potential of perovskite/graphene structures, a comprehensive understanding of their properties is still needed. High magnetic fields are invaluable for interrogating fundamental physical processes Stable all-inorganic CsPbX 3 perovskite nanocrystals (PNCs) with high optical yield can be used in combination with graphene as photon sensors with high responsivity (up to 10 6 A W −1 ) in the VIS-UV range.…”
mentioning
confidence: 99%
“…20 Takhee Lee et al reported photo-responsive molecular junctions enhanced by different intrinsic dipole moments. 21 The dipole interaction in a liquid environment could also influence the measured tunneling current by the STM break junction technique. 22–24…”
Section: Introductionmentioning
confidence: 99%
“…20 Takhee Lee et al reported photo-responsive molecular junctions enhanced by different intrinsic dipole moments. 21 The dipole interaction in a liquid environment could also influence the measured tunneling current by the STM break junction technique. [22][23][24] This paper demonstrates that the charge transport measurements under different aqueous solutions can, to a certain extent, recognize molecule-originated transport signals and be applied to studying the charge transport through fully hydrated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…the molecular-scale is the primary objective and a prerequisite toward realizing commercial molecular electronic device applications. [7][8][9][10][11][12][13][14] In this context, molecular optoelectronics have emerged as a promising field capable of controlling the device characteristics using light as a physical stimulus, as well as assisting the comprehension of the intrinsic transport behavior through the interaction between molecular orbital level and light. [11][12][13][15][16][17][18][19][20][21][22][23] In the infancy of this field, Yasutomu et al were the first to report molecular photodiode systems based on two different types of self-assembled monolayers (SAMs) of helical peptides possessing selective excitation molecular groups.…”
mentioning
confidence: 99%